An African Girl's Journey to Financial Freedom - Ugwu, Arese (Nigeria, 2016)
This book tackles, debt, spending, the consumerist culture of the African middle class, the fear and misconceptions surrounding money and the lack of it, love, friendships, cultural and societal pressures and the roles they play in success. With each chapter comes a Smart Money Lesson, there to help you work your way up the financial ladder.
Keywords: Finance; Investments; Non-Fiction